2017
DOI: 10.1021/acs.jpcb.7b04706
|View full text |Cite
|
Sign up to set email alerts
|

Complex Permittivity of Ionic Liquid Mixtures Investigated by Terahertz Time-Domain Spectroscopy

Abstract: Ionic liquids are salts found in their liquid state at ambient temperature. The physicochemical properties of ionic liquids can be tailored by selecting constituent cation and anion from numerous available ions. The physicochemical properties can be further tuned by mixing different neat ionic liquids. Reported data of ionic liquid mixtures reveal that frequently investigated properties such as density, viscosity, and thermal stability follow corresponding mixing laws. Complex permittivity in the interval of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Reichenbach et al proposed that the two components included within the broad low-frequency band seen in the FIR spectra of RTILs (see the right panel of Figure ) arise from LO–TO splitting. Considering once more the Lydane-Sachs-Teller relation and ε s and ε ∞ values for [C 4 C 1 Im]­[NTf 2 ], , the resulting value for (ω LO /ω TO ) 2 is 3.83 ± 0.39, which should be compared to the corresponding value (3.05 ± 1.12) for the two components of the curve fit of the FIR spectrum. As shown in Figure S1, we remark that including or not the TO mode has only a marginal impact on the quality of the fit of FIR spectrum of [C 4 C 1 Im]­[NTf 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reichenbach et al proposed that the two components included within the broad low-frequency band seen in the FIR spectra of RTILs (see the right panel of Figure ) arise from LO–TO splitting. Considering once more the Lydane-Sachs-Teller relation and ε s and ε ∞ values for [C 4 C 1 Im]­[NTf 2 ], , the resulting value for (ω LO /ω TO ) 2 is 3.83 ± 0.39, which should be compared to the corresponding value (3.05 ± 1.12) for the two components of the curve fit of the FIR spectrum. As shown in Figure S1, we remark that including or not the TO mode has only a marginal impact on the quality of the fit of FIR spectrum of [C 4 C 1 Im]­[NTf 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…1720 The low-frequency intermolecular vibrational modes have been studied by using far IR (FIR) spectroscopy and terahertz time-domain spectroscopy (THz-TDS). 2129 In determining the center frequencies of the broad absorption band below 150 cm –1 for some imidazolium-based ILs, the major contribution of the force constant in the angular frequency of the harmonic oscillator, ω = ( k /μ) 1/2 , and the significance of the local and directional hydrogen bond were pointed out. 2224 On the other hand, we previously reported that THz-TDS and FIR spectroscopy can directly explore the intermolecular vibrations because of the cation–anion interactions in methylimidazolium ILs that originated in Coulomb interactions and hydrogen-bond-type interactions and argued that the central frequencies of intermolecular vibrations are on the essential contribution of the reduced mass μ calculated from the respective masses of the methylimidazolium ring cation [mim + ] and the anion [A – ] as well as the force constant k, which was established for a wide variety of methylimidazolium ILs.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of THz spectroscopy in fundamental science is obvious because many important low-energy excitations are present within this range in practically all kind of materials: emerging materials [2], semiconductors [3], ferroelectrics [4], superconductors [5], polymers [6], photonic crystals [7], liquids [8][9][10], gases [11] and biological systems [12]. Moreover, THz technology has a high impact in many different areas too.…”
Section: Introduction 11 Brief Introduction On Terahertz Radiationmentioning
confidence: 99%